Sistem Perawatan Alat Overhead Crane Dengan Metode Reliability Centered Maintenance (RCM) II dan Age Replacement - Ferdiansyah Wendyantoro; Indah Apriliana Sari Wulandari (Physical Sciences, Life Science and Engineering, 2026)
Equipment maintenance is very important to ensure that the equipment operates properly within a certain period of time. PT. XYZ, which is engaged in the shipping industry, uses a demag type overhead crane with a capacity of 5 tons in its production process. This study aims to evaluate the reliability level of overhead cranes in existing conditions by calculating the reliability value. In addition, this study also aims to determine the critical component replacement interval appropriately so that replacement is carried out before downtime occurs. The results of the study identified three critical components, namely Contactor, Photoelectric Sensor, and Motor Hoist, with MTTR values ​​of 3.65667 hours, 4.15333 hours, and 1.1546 hours, respectively. The application of the age replacement method showed an increase in reliability: Contactor 39%, Photoelectric Sensor 40%, and Motor Hoist 83%. The recommended component replacement interval is every 11 days to reduce downtime and increase operational efficiency.